Identifying multiple sclerosis subtypes using unsupervised machine learning and MRI data - Arman Eshaghi (Nature Portfolio, 2021)
Multiple sclerosis is a heterogeneous progressive disease. Here, the authors use an unsupervised machine learning algorithm to determine multiple sclerosis subtypes, progression, and response to potential therapeutic treatments based on neuroimaging data.